A new model for the diagnostic assessment services trajectory for neurodevelopmental conditions - Jacques, Claudine; Rivard, Mélina; Mello, Catherine; Abouzeid, Nadia; Hérault, Élodie; Saulnier, Geneviève (Frontiers in Rehabilitation Sciences, 2024)
PurposeThe Canadian province of Québec faces several issues regarding the accessibility and quality of diagnostic assessment and the efficiency and continuity of evaluation, support, and intervention services for children with neurodevelopmental conditions (NDCs). To address these issues, the Ministry of Health and Social Services mandated a research team to initiate the development of a reference trajectory, i.e., a proposed model pathway based on national and international best practices and research, for the diagnostic assessment of NDCs in children aged 0–7 years.MethodsThe present study focused on the development of a logic model to operationalize the diagnostic services trajectory using a community-based participatory research approach and informed by implementation science. This involved representatives from multiple stakeholder groups (e.g., parents, professionals, physicians, administrators, researchers). Project steps included an analysis of best practices from a literature review on diagnostic trajectories, focus groups and interviews with stakeholders, and a validation process to ensure the appropriateness of the final model.ResultsThe integration of existing research and stakeholder input resulted in a logic model for a new diagnostic services trajectory for children aged 0–7 years suspected of NDCs and identified key ingredients that should be present in its future implementation.ConclusionThe proposed model for a diagnostic services trajectory is expected to address several systemic issues identified previously. Its implementation will need to be evaluated to ensure its sustained focus on the needs of families and its ability to promote their quality of life, well-being, and involvement.